Focus group discussion on HIV/AIDS risk behaviors in a fishermen's community of east coast, Malaysia - Samsuddin, Niza; Ali, Aishah; Md Aris, Mohd Aznan; Draman, Samsul (2009)
There is a need to examine risk factors contributing to the high prevalence of HIV/AIDS in the fishermen's communities. A qualitative study by using focus group discussion method was conducted in one of the fishermen's village of East Coast, Malaysia. A total of thirty-five people were recruited and five focus group discussions of 6-9 people were conducted over a period of 7 months. The selection of participants was based on villagers that were able to give the best information about the topic being discussed. Structured open ended questionnaires were used to ensure consistency approach between facilitators. All sessions were video-taped with respondent's consent. The discussions were transcribed per verbatim and several contentious themes were developed. Every respondent agreed that HIV/AIDS is an immense problem in the village. Many of the villagers were involved in HIV/AIDS risk behaviors. Multiple sex partners, smoking, alcohol abuse, glue sniffing, intravenous drug abusing and ketum leaves addictions were being practiced freely in the village. Children start to smoke and glue sniff as early as eight years old. Easy accessibility of all the substances in the village and lack of support and supervision from parents and ignorance and lack of recreational and religious activities instigated them to involve in high risk behaviors. Negative stigma towards drug abusers hindered them from involvement in behaviors in the community which are interrelated to each other and lead to high HIV/AIDS prevalence in the community. For effective HIV/AIDS preventive and control measures in the fishermen's community, the researchers recommended integrated approach of actions by various group of people and agencies.